Quota Allocation in International Fisheries - Cox, Anthony (OECD Publishing, 2009)
Developing an allocation scheme for distributing rights amongst fishing nations is a key issue in the development of stable cooperative arrangements to exploit international fish resources. Allocation within regional fisheries management organisations (RFMOs) is generally based on the historical catches of parties to the RFMOs. However, as membership of RFMOs increases and pressure to allow additional countries, particularly coastal developing countries, to participate meaningfully in international fisheries intensifies, there is increasing policy attention being paid to the issue of allocation of rights in RFMOs. This paper explores issues relating to the process of allocating participatory rights in RFMOs, especially in those cases in which one or more fisheries remain unallocated, and is intended to stimulate discussion among policy makers on possible policy directions in such situations without directly or indirectly evaluating existing allocation schemes. The paper reviews the international legal framework governing international fisheries, the economic issues underlying allocations, and the current state of play in the allocation regimes in RFMOs. A broader perspective on the allocation issue is provided by examining the experiences of other resource sectors that have wrestled policy challenges similar to those confronting international fisheries in allocating participatory rights amongst current and potential participants - water resources; and greenhouse gases - to see if they offer any transferable insights on the issue
Keywords: Agriculture and Food